Fluorescent Tracers for In Vivo Imaging of Lymphatic Targets - Russell, P. S.; Velivolu, R.; Maldonado Zimbrón, V. E.; Hong, J.; Kavianinia, I.; Hickey, A. J. R.; Windsor, J. A.; Phillips, A. R. J. (Frontiers in Pharmacology, 2022)
The lymphatic system continues to gain importance in a range of conditions and therefore imaging of lymphatic vessels is becoming more widespread for research, diagnosis, and treatment. Fluorescent lymphatic imaging offers advantages over other methods in that it is affordable, higher resolution, and does not require radiation exposure. However, because the lymphatic system is a one-way drainage system, successful delivery of fluorescent tracers to lymphatic vessels represents a unique challenge. Each fluorescent tracer used for lymphatic imaging has distinct characteristics, including size, shape, charge, weight, conjugates, excitation/emission wavelength, stability, and quantum yield. These characteristics in combination with the properties of the target tissue affect the uptake of the dye into lymphatic vessels and the fluorescence quality. Here we review the characteristics of visible wavelength and near-infrared fluorescent tracers used for in vivo lymphatic imaging, and describe the various techniques used to specifically target them to lymphatic vessels for high quality lymphatic imaging in both clinical and pre-clinical applications. We also discuss potential areas of future research to improve lymphatic fluorescent tracer design.